An Investment-and-Marriage Model with Differential Fecundity - Hanzhe Zhang (Center for Economic Studies and ifo Institute (CESifo), 2019)
I build an equilibrium investment-and-marriage model to explain stylized facts about education, income, and marriage for Americans born in the twentieth century that had not been explained in a unified way. The most novel finding is a theoretical explanation for why women attend college at a higher rate and earn a lower average income than men. Differential fecundity and an equilibrium marriage market form the basis of my explanation. The model also accounts for gender-specific relationships between age at marriage and income, as well as the evolving relationship between age at marriage and spousal income for women. I provide evidence to support my theory and calibrate the model to conduct counterfactual analyses.
Keywords: C78; D10; 330; college gender gap; earnings gender gap; marriage age; nonassortative matching